The evolution of industrial production "models" under the sustainability perspective - César, Francisco I. Giocondo (Revista Hipótese, 2015)
The objective of this work is to carry out a literature review of the evolution of industrial production “models” and its evolution from the traditional process where focused cost, quality and time to sustainable production model which considers environmental quality, social equity and healthy economy. In total of seven production models were studied (Compliance Management, Control end of pipe, prevention of pollution, cleaner production, eco-efficiency, green Production, Sustainable Production). A literature review was conducted to provide a comprehensive understanding of each model, and tends to emphasize similarities and minimize differences, trying to emphasize its features and its evolution.
Keywords: Literature review; Industrial production; Sustainability; Sustainable production